Differences in the accessibility of methylated and unmethylated DNA to DNase I. - Kochanek, S (1993)
DNase I binds in the minor groove of DNA and is used as an enzymatic tool to investigate the interaction of proteins with DNA. Here we show that the major groove located 5-methyldeoxycytidine can enhance or inhibit the cleavage rates of DNA by DNase I. This effect may be caused in part by changes in DNA structure affecting the accessibility of the minor groove of DNA to DNase I.